PENGARUH FAKTOR INTERNAL BANK TERHADAP PENYALURAN KREDIT PERBANKAN - Nabila Sabrina Asma Sinaga Sinaga; Gregorius N. Masdjojo (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
Banking is one of the business entities that collects funds from the people in the form of savings and distributes them back to the people in the form of credit or in the form of savings in order to raise the standard of living of the people. The population of this study are banking companies registered with the Financial Services Authority (OJK) in the 2016-2020 period. The sampling technique in this study uses the panel data regression method, with a total of 50 banking companies that issue financial statements according to predetermined criteria. The results of this study indicate that the Loan to Deposit Ratio (LDR) variable simultaneously has a significant effect on bank lending. Meanwhile, Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Return On Assets (ROA), Net Performing Loans (NPL), and Operating Expenses on Operating Income (BOPO) have no significant effect on bank lending.